2020
DOI: 10.1177/1129729820913378
|View full text |Cite
|
Sign up to set email alerts
|

Simulation training on bedside veno-arterial extracorporeal membrane oxygenation decannulation

Abstract: Veno-arterial extracorporeal membrane oxygenation is a form of mechanical circulatory support for patients with refractory decompensated heart failure. Blood is drawn from a large vein and pumped back to a large artery, usually a femoral artery through large bore catheters. When the heart recovers, the extracorporeal membrane oxygenation support can be terminated and the catheters are decannulated. The bleeding at the venous side can be controlled by prolonged compression; however, the arteriotomy wound needs … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 5 publications
0
4
0
Order By: Relevance
“…Of these, 11% provided reading materials or written guides ( 27 , 32 , 38 , 50 ), and 11% provided online instruction ( 21 , 38 , 40 , 47 ). Multimedia was used infrequently, with video instruction in 11% ( 31 , 35 , 38 , 41 ), video-assisted simulation feedback in 8% ( 20 , 39 , 44 ), and augmented reality in 3% ( 40 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Of these, 11% provided reading materials or written guides ( 27 , 32 , 38 , 50 ), and 11% provided online instruction ( 21 , 38 , 40 , 47 ). Multimedia was used infrequently, with video instruction in 11% ( 31 , 35 , 38 , 41 ), video-assisted simulation feedback in 8% ( 20 , 39 , 44 ), and augmented reality in 3% ( 40 ).…”
Section: Resultsmentioning
confidence: 99%
“…The vast majority of ECMO education in the post-H1N1 era incorporates hands-on SBME, occasionally integrating video instruction/feedback ( 31 , 35 , 39 , 41 , 44 ), augmented reality ( 40 ), or online simulators ( 21 ). This is consistent with findings that 72% of recently surveyed ELSO centers reported having or developing ECMO simulation programs ( 7 ).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the knowledge measurement tool in this study was intended to simply measure if the subjects had correct or wrong knowledge, which might be unable to detect signi cant differences in the knowledge level between the experimental and the control groups. Several previous studies that trained medical staff on ECMO simulation and evaluated their performance have shown the effects on performance [13][14][15]17]. Thus, future studies should verify the effectiveness of the ECMO nursing VR simulation program using tools evaluating empirical knowledge and nursing performance skills.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, ECMO training has been dominated by instructor-centered training methods such as lectures and skills training. However, some training using e-learning and high-delity simulators have been conducted recently [12][13][14][15][16][17][18]. Some preceding studies have shown that training using high-delity simulators has no difference in effectiveness when compared to traditional training [17].…”
Section: Introductionmentioning
confidence: 99%